The role of oxidation damage in fatigue crack initiation of an advanced Ni-based superalloy. (December 2015) - Cruchley, S.; Li, H.Y.; Evans, H.E.; Bowen, P.; Child, D.J.; Hardy, M.C.
Highlights: Pre-oxidised Ni-based superalloy RR1000 was tested under high cycle fatigue at room temperature. Both negative and positive effects of pre-oxidation are observed. The critical stress of oxide cracking under fatigue ( R  = 0.1) is between 700 and 800 MPa. Improved fatigue strength is also observed above this critical stress and is optimised at 900 MPa. Mechanisms for contrasting effects are proposed. Abstract: The effects of prior oxidation on the room temperature fatigue life of coarse-grained Ni-based superalloy, RR1000, have been investigated. High cycle fatigue tests were conducted, on both machined and pre-oxidised testpieces, at room temperature at an R ratio of 0.1. The oxidation damage was produced by pre-exposures at 700 °C for either 100 or 2000 h. Pre-oxidised testpieces tended to fail with shorter fatigue lives than those obtained from the as-machined testpieces although they were also observed to outperform the as-machined test pieces at peak stress levels around 900 MPa. The chromia scale and intergranular alumina intrusions formed during pre-oxidation are prone to crack under fatigue loading leading to early crack nucleation and an associated reduction in fatigue life. This has been confirmed to be the case both below and above a peak stress level of ∼900 MPa. The better fatigue performance of the pre-oxidised specimens around this stress level is attributed to plastic yielding of the weaker γ′ denuded zone, which effectively eases the stress concentration introduced by the cracking of the chromia scale and intergranular internal oxides. This γ′ denuded zone is also a product of pre-oxidation and develops as a result of the selective oxidation of Al and Ti. Over a limited stress range, its presence confers a beneficial effect of oxidation on fatigue life.